Estimating forced labour: from a legal category to a statistical category for international political campaigns - Schalkowski, Nicola; Renard, Léa (International review of sociology, 2024)
This article contributes from a sociology of knowledge perspective to the ongoing sociological debate about statistics produced by international organisations taking the Global Estimates of Forced Labour published by the International Labour Organization (ILO) as a case of international quantification. We ask: what stages of negotiation were involved in the transformation of a legal category into a statistical category of forced labour oriented towards political action? The analysis combines the historical reconstruction of the political and organisational processes behind the production of the estimates with the study of the measurement framework of forced labour. The qualitative case study is based on semi-structured expert interviews and ILO documents. Our results highlight the processes by which a legal category was made practicable for statistical work and thereby point to the specific arrangements and connections between law, statistics, and policy within international organisations. As we argue, the estimates have provided consistency to a fragile social construct that originated in the imperial context of the interwar period, and that was turned into a ‘visible’ social and global phenomenon of the twenty-first century.